An open, non-randomised, phase 1/2 trial on the safety, tolerability, and immunogenicity of single-dose vaccine “Sputnik Light” for prevention of coronavirus infection in healthy adults - Amir I. Tukhvatulin (Elsevier, 2021)
Background: While the world is experiencing another wave of COVID-19 pandemic, global vaccination program is hampered by an evident shortage in the supply of licensed vaccines. In an effort to satisfy vaccine demands we developed a new single-dose vaccine based on recombinant adenovirus type 26 (rAd26) vector carrying the gene for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike (S) glycoprotein – “Sputnik Light”. Methods: We conducted an open label, prospective, non-randomised phase 1/2 trial aimed to assess safety, tolerability, and immunogenicity of “Sputnik Light” vaccine in a single center in Russia. Primary outcome measures were antigen-specific humoral immunity (Anti-RBD-SARS-CoV-2 antibodies measured by ELISA on days 1, 10, 28, and 42) and safety (number of participants with adverse events monitored throughout the study). Secondary outcome measures were antigen-specific cellular immunity (measured by antigen-dependent CD4+ and CD8+ T-cell proliferation, number of antigen-specific interferon-γ-producing cells as well as interferon-γ concentration upon antigen restimulation) and change in neutralizing antibodies (measured in SARS-CoV-2 neutralization assay). Findings: Most of the solicited adverse reactions were mild (66·4% from all vaccinees), few were moderate (5·5%). No serious adverse events were detected. Assessment of Anti-RBD-SARS-CoV-2 antibodies revealed a group with pre-existing immunity to SARS-CoV-2. Upon this finding we separated all safety and immunogenicity data based on pre-existing immunity to SARS-CoV-2. There were notable differences in the vaccine effects on immunogenicity by the groups. Vaccination of seropositive (N=14) volunteers rapidly boosted RBD-specific IgGs from reciprocal geometric mean titer (​GMT) 594·4 at a baseline up to 26899 comparing to 29·09 in seronegative group (N=96) by day 10. By day 42 seroconversion rate reached 100% (93/93) in seronegative group with GMT 1648. At the same time, in the seropositive group, seroconversion rate by day 42 was 92·9% (13/14) with GMT 19986. Analysis of neutralizing antibodies to SARS-CoV-2 showed 81·7% (76/93) and 92·9% (13/14) seroconversion rates by day 42 with median reciprocal GMT 15·18 and 579·7 in the seronegative and seropositive groups, respectively. Antigen-specific T cell proliferation, formation of IFNy-producing cells, and IFNy secretion were observed in 96·7% (26/27), 96% (24/25), and 96% (24/25) of the seronegative group respectively and in 100% (3/3), 100% (5/5), and 100% (5/5) of the seropositive vaccinees, respectively. Interpretation: The single-dose rAd26 vector-based COVID-19 vaccine “Sputnik Light” has a good safety profile and induces a strong humoral and cellular immune responses both in seronegative and seropositive participants. Funding: Russian Direct Investment Fund.